2002
DOI: 10.1097/00005537-200201000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intranasal Azelastine on the Response to Nasal Allergen Challenge

Abstract: The effects of intranasal azelastine are similar to those of oral second-generation antihistamines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
(28 reference statements)
2
18
0
1
Order By: Relevance
“…This is consistent with previous findings of increased levels of nasal proteins, namely ECP, IL-5, IL-13, and albumin, after allergen challenge. [27][28][29] The increase in levels of T H 2 cytokines and ECP in response to EEC ragweed exposure in nasal lavage specimens could be reduced by both JNJ-39220675 and pseudoephedrine. However, the accompanying reduction in albumin levels seen with both compounds suggests that this is due to vasoconstriction with an accompanying reduction in the size of the turbinates and is not an anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous findings of increased levels of nasal proteins, namely ECP, IL-5, IL-13, and albumin, after allergen challenge. [27][28][29] The increase in levels of T H 2 cytokines and ECP in response to EEC ragweed exposure in nasal lavage specimens could be reduced by both JNJ-39220675 and pseudoephedrine. However, the accompanying reduction in albumin levels seen with both compounds suggests that this is due to vasoconstriction with an accompanying reduction in the size of the turbinates and is not an anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…6,43 Topical antihistamines, delivered by means of nasal spray, avoid or minimize systemic side effects. Azelastine used topically reduced rhinorrhea but failed to reduce congestion in one study, 44 although not in another. 45 Thus the debate on the benefits of antihistamines on nasal congestion continues.…”
Section: Therapy Of Allergic Rhinitis Improves Associated Sleep Distumentioning
confidence: 93%
“…42,53,54 Azelastine, an intranasal antihistamine with anti-inflammatory properties, has reduced nasal congestion and improved subjective sleep quality in small studies, but was also found to cause somnolence. 55,56 Decongestants are sympathomimetic drugs that constrict capacitance vessels in the turbinates and decrease nasal congestion. 46 Intranasal formulations act quickly, but their utility is limited by congestion rebound (rhinitis medicamentosa) that can occur after just a few days of regular use.…”
Section: 24mentioning
confidence: 99%